Protection and the Own-Funds Window in Tanzania : An Analytical Framework and Estimates of the Effects of Trade Liberalization - DeRosa, Dean. (Washington, D.C. : International Monetary Fund, 1991)
This paper presents a simple partial equilibrium framework for considering the economic implications of administered protection in Tanzania, against the background of the country's parallel exchange market and the establishment of the own-funds and open general license (OGL) facilities for authorizing imports. It also presents estimates of the range of possible adjustment in the real exchange rate and trade flows following from a unification of the highly-fragmented import licensing system, coupled with sufficient liberalization of the OGL facility to eliminate own-funded imports and the incentive to export smuggling.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet